INNOVATIVE APPROACHES TO THE INTERPRETATION OF ABSCISSIAL AND ORDINAL INTERDISCIPLINARY CONNECTIONS IN THE EDUCATIONAL PROCESS (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
The article explores innovative approaches to the interpretation and application of abscissial (horizontal) and ordinal (vertical) interdisciplinary connections within the educational process. Theoretical and methodological foundations are analyzed, emphasizing the importance of integrating these connections to foster holistic knowledge acquisition, critical and creative thinking, and competence-based learning. It is argued that innovative pedagogical strategies-such as project-based learning, digital technologies, and STEAM education-significantly enhance the effectiveness of abscissial and ordinal integration in modern education.